Versatility of the Greater Saphenous Fasciocutaneous Perforator Flap in Coverage of the Lower Leg - Lu, Shengdi; Wang, Chunyang; Wen, Gen; Han, Pei; Chai, Yimin (Journal of Reconstructive Microsurgery, 2014)
Paucity of soft tissue locally available for reconstruction of defects in the leg and foot remains a challenge. Greater saphenous fasciocutaneous perforator flap in reconstruction of the lower leg has been used effectively to cover these defects. In many situations, it is a viable alternative to free flaps and cross-leg flap reconstruction. The objective of this retrospective study was to evaluate the efficacy of the greater saphenous fasciocutaneous perforator flap for reconstruction of the medial and anterior lower leg, medial malleolus, and hind foot. A total of 26 patients with soft tissue defects of the medial and anterior lower leg, medial malleolus, and hind foot were evaluated. Preoperative data, age, sex, defect etiology, defect size, flap dimension, postoperative results, and complications were recorded. All patients were followed up postoperatively. The procedure was uneventful in 25 of 26 patients. The one unsuccessful flap developed partial necrosis of the distal edge due to venous congestion, and secondary healing was achieved by conservative treatment. No patient showed signs of infection. The defect etiology in all patients was trauma of the lower extremity or its complications, most frequently open fracture (19 patients), followed by osteomyelitis of the tibia (2 patients). The greater saphenous fasciocutaneous perforator flap is versatile, reliable, and useful in coverage of medial and anterior lower leg, malleolus, and hind foot defects. This surgical technique is a safe, short-duration alternative to microsurgical reconstruction.
Keywords: perforator flap; saphenous nerve; lower leg